Adapting elements of market value coverage in adoption and diffusion of innovations - fast food industries (preliminary study) - Nezakati, Hossein; Ali, Noor Azman; Mansori, Shaheen; Ang, Siew Hui (American-Eurasian Network for Scientific Information, 2011)
Intensive completion in fast food industry force the companies to develop new recopies as well as implement the innovative marketing and business strategies to capture the higher market share in industry. However, the large numbers of innovative ideas and products have been failure in market because they could not find the right channel to approach the customers. To get the better perspective regarding this issue, this study develops the model, which can explain the reasons why sometime customers are not keen to purchase from particular brand or location. The proposed model explains that how the four product/service characteristics 4As (affordability, awareness, acceptability,accessibility) can influence various groups of consumers by different level of innovativeness. In particular, this model aim to explain how innovators, early adaptor, early majority, late majority and laggards as five categories of customers based on Diffusion of Innovations theory react toward 4As.